ZnO and MXenes as electrode materials for supercapacitor devices - Ammar, Ameen Uddin; Yildirim, Ipek Deniz; Bakan, Feray; Erdem, Emre (Beilstein Journal of Nanotechnology, 2021)
Supercapacitor devices are interesting owing to their broad range of applicability from wearable electronics to energy storage in electric vehicles. One of the key parameters that affect the efficiency of supercapacitor devices is selecting the ideal electrode material for a specific application. Regarding this, recently developed metal oxides, specifically nanostructured ZnO, and MXenes with their defect structures, size effects, as well as optical and electronic properties have been presented as electrode material in supercapacitor devices. The discussion of MXenes along with ZnO, although different in chemistry, also highlights the differences in dimensionality when it comes to defect-driven effects, especially in carrier transport. The volume under the influence of the defect centers is expected to be different in bulk and 2D structures, regardless of composition. Hence, analysis and discussion of both materials provide a fundamental understanding regarding the manner in which 2D structures are impacted by defects compared to bulk. Such an approach would therefore serve the scientific community with the material design tools needed to fabricate the next generation of supercapacitor devices.
Keywords: 2D materials; electrodes; MXenes; supercapacitors; zinc oxide (ZnO)